The Influence Of Organizational Culture, Job Characteristics, And Transformational Leadership On Employee Engagement of PT. Texttile Indonesia - Rio Haribowo; Fitri Rezeki (Cita Konsultindo Research Center, 2023)
Human resources are a very important thing and must be owned in an effort to achieve organizational or corporate goals and most importantly to achieve a goal in the company. The most basic thing in achieving this goal is how the company is able to direct employees in a positive direction, namely by paying attention to the attachment of its employees, it can produce human resources that are able to be qualified and human resources that are able to compete. This type of research uses statistical analysis methods through the application of SPSS Vers. 28, this sampling used a random sample technique with a total sample of 86 respondents. This study aims to test, review, and obtain the results of the influence of Organizational Culture, Job Characteristics and Transformational Leadership on PT Employee Engagement. Yan Jin Indonesia. The results of this study show that: (1) there is no partially significant influence between employee organizational culture and employee engagement of PT employees. Yan Jin Indonesia. (2) does not have a positive effect on the employee engagement of PT. Texttile Indonesia. (3) There is a positive and significant influence on transformational leadership with PT. Texttile Indonesia.